Development of Automatic Water Pump On-Off Device for Durian Orchard Case Study of Durian Conservation Orchard, Nonthaburi, Rajapruk University - โพธิ์แจ้ง ณัฐชนก; ยิ่งยง อิทธิพล; สิริไพบูลย์กาญจน์ ชัยวัฒน์; ธีรานุตร พฤกษ์ภูมิ; ทับพร รสสุคนธ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) develop an automatic water pumping system on-off device for durian orchards that can measure water level and control water drainage both automatically and via smartphone for more efficient water management, and 2) find satisfaction with water management in durian orchards using Internet of Things (IoT) technology and sensor system to measure and control water volume to reduce water stagnation or water shortage in the dry season. The population in this research is people involved in water management in durian orchards at Rajapruk University, who are the supervisors of the Nonthaburi Durian Conservation Project. The sample group was purposively selected as the Nonthaburi Durian Conservation Orchard at Rajapruk University. The statistics used in the research included mean and standard deviation. The research results found that 1) the automatic water pumping system on-off device, automatic water drainage control system via wireless sensor to prevent water stagnation in the rainy season, consisted of 3 parts: (1) value receiving part, (2) control and command part, and (3) device that displays system performance via wireless network efficiently. 2) The study of farmers’ satisfaction with the automatic watering control system via wireless sensor for water drainage found that the average efficiency level of the system is 4.69 farmers had the highest overall satisfaction.